Community Participation in the Development of the Saluleang Mangrove Tourism Area in Bebanga Kelurahan Kalukku District, Mamuju Regency - Nirwana Sari; Abd Malik; Maddatuang Maddatuang (UNM Geographic Journal, 2020)
The Saluleang mangrove ecotourism area, Bebanga Village, Kalukku District, Mamuju Regency is a developed ecotourism area, the management carried out by the community and the lack of policy support has made Saluleang mangrove ecotourism not widely known by the public. Ecotourism is a form of management that can contribute to the environment and surrounding communities. This study aims to determine: 1) Forms of community participation in mangrove forest management in the development of the Saluleang ecotourism area 2) The level of community participation in mangrove forest management activities in developing ecotourism areas. The population in this study were all residents of Bebanga Village, amounting to 8006 people. The sample in this study amounted to 100 people. This research is quantitative descriptive. Data collection techniques include observation, questionnaires and documentation. Data analysis was performed using descriptive analysis and Likert scale. Based on the research results, the form of participation that was mostly carried out by the community was the form of participation in the form of labor, namely 44%. The level of community participation in ecotourism development is in the 27-30 interval with a very high category. The results of the test on the effect of community participation in the Saluleang Ecotourism Development were 75.60% and 24.40% were influenced by other factors outside the participation and development variables.